Time-varying capital requirements and disclosure rules: Effects on capitalization and lending decisions - Björn Imbierowicz; Jonas Kragh; Jesper Rangvid (Deutsche Bundesbank, 2018)
We investigate how banks' capital and lending decisions respond to changes in bankspecific capital and disclosure requirements. We find that an increase in the bankspecific regulatory capital requirement results in a higher bank capital ratio, brought about via less asset risk. A decrease in the requirement implies more lending to firms but also less Tier 1 capital and higher bank leverage. We do not observe differences between confidential and public disclosure of capital requirements. Our results empirically illustrate a tradeoff between bank resilience and a fostering of the economy through more bank lending using banks' capital requirement as policy instrument.
Keywords: G21; G28; 330; capital requirement; bank lending; bank capital structure; capital disclosure rules